Analisis Kegiatan Pengembangan Koleksi Open Library Telkom University - Tyas, Zahra Wenning (Perpustakaan Nasional, 2024)
As an effort to meet the needs of users and realize its position as a center of science and information sources through the collection of library collections, Open Library Telkom University carries out a collection development process. Research about collection development at Open Library Telkom University is important, to explain the stages of collection development and analyze the suitability of collection development activities at Open Library Telkom University with the principles of collection development. The purpose of this research is to analyze and explain the stages of collection development at Open Library Telkom University. The methods used in this research are descriptive qualitative methods and data collection techniques carried out through observation, interviews, and literature studies. The findings of this research that collection development at Open Library Telkom University includes user needs analysis activities through a library collections needs analysis survey that is distributed to the study program, carrying out collection development activities in accordance with established policies, selecting library collections, procuring libraries tailored to the type of library and user needs, carrying out weeding of library collections, and evaluation of library development activities. Collection development activities at Open Library Telkom University have been carried out systematically and in accordance with the stages and principles of collection development.